A circle with center coordinates (a,b) and radius r can be expressed as;

`(x-a)^2+(y-b)^2 = r^2`

`x^2-2ax+a^2+y^2-2by+b^2 = r^2`

`x^2+y^2-2ax-2by+a^2+b^2 = r^2`

`x^2+y^2-2ax-2by+(a^2+b^2-r^2) = 0` ---(1)

Now let us arrange `x^2+y^2+4x+6y+12=0` same as (1)

`x^2+y^2+4x+6y+12=0 `

`x^2+y^2-2(-2)x-2(-3)y+12 = 0`

Now this is identical with (1)

a = -2

b = -3

`(a^2+b^2-r^2) = 12`

`(-2)^2+(-3)^2-r^2 = 12`

` 4+9-r^2 = 12`

`r^2 = 13-12`

` r = 1` since r>0

**So the center is (-2,-3) and radius is 1.**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now